The three pillars of sustainability in education: the sistemic approach of social responsibility - MOLINA, JAIRO EDUARDO; Peña, Armando; Hurtado, Edinson (Technium Sustainability, 2022)
Sustainability should be a cross-cutting theme within the curriculum as a set of essentially attitudinal teaching contents that should become part of the activities proposed in all educational areas. Their incorporation means formalizing an education in values and attitudes not sporadically but constantly throughout each course. However, it is also a poorly understood term that needs to be correctly identified to carry out more effective actions within an educational institution. A topic is transversal if it is important for development and needs, for its success, many teachers from different areas to be involved in it. Therefore, the Universidad del Atlántico in Barranquilla, Colombia is committed to this multidisciplinary project. Three students from 15 classrooms from 3 different careers have been taken to carry out this educational project. This is an analytical observational study of qualitative nature, where the researchers simply attempt to systematically describe the characteristics of categories, and phenomena, then compare constructs and postulates generated from phenomena observed in research context, as well as to discover causal relationships, but avoid assuming a priori constructs or relationships. The general conclusion of the study is that there is a need to broaden the horizons of this study to a much wider population and not only to the educational sector.